Economic and environmental assessment using emergy of a geothermal power plant. (15th January 2021) - Jalili, Mohammad; Chitsaz, Ata; Hashemian, Mehran; Rosen, Marc A.
Abstract: Environmental and economic factors are among the most important in thermodynamic systems design. To evaluate energy production systems from economic an environmental viewpoints, exergoeconomic and exergoenvironmental analyses are sometimes used. In this research, the concept of emergy is used for economic and environmental studies to improve understanding. Emergy expresses all the inputs and outputs of a system based on a specific type of energy (usually solar energy) that is required to generate the input or output. In order to enhance energy-based emergy, it is converted to exergy-based emergy here and, using the specific exergy costing (SPECO) method, emergy-based exergoeconomic and emergy-based exergoenvironmental balances are written for the components of a system. The present economic and environmental assessment based on emergy is carried out on a combined flash and binary geothermal system. The results of this study show that the economic emergy factor and the ecological emergy factor of the system are 34.1% and 4%, respectively. Therefore, to reduce the amount of destruction emergy, strategies must be adopted. Highlights: The concept of emergy has been carefully studied. The emergy based economic and environmental method is selected for analyses. Component related monetary and ecological emergy is considered. Combined flash and binary geothermal system is selected for power and heat generation. Systems energy and exergy efficiency is 54% and 64% respectively.